Stereoselektivitas Reaksi Aldol dalam Sintesis C1-C12 Senyawa Epotilon - Muharram Muharram; Dieter Schinzer (Institut Teknologi Bandung, 2009)
The retrosynthesis analysis shows that the synthesis of epothilone is built from three main fragments, which are ethyl ketone 5, thiazole 3, and aldehyde 4 fragments. The three fragments are coupled by aldol reaction, esterification or macrolactonisation, and olefin-epoxide metathesis. The aldol reaction was conducted in synthesis of C1-C12 epothilone from ethyl ketone 5 and chiral aldehyde 4a with highly stereoselective (97% ee) at temperature -78 Â°C and used lithium diisopropylamine (LDA) as a base. The ethyl ketone was synthesized from the Î±-bromoester 10 and diethyl ketone 11 with a good yield in each of eight stages of reaction. The chiral aldehyde 4a was synthesized from 6-heptenoic acid 19 through Â six steps reaction and Evans-Auxiliary 21.